PENERAPAN ROLE PLAY DALAM BASIC ENGLISH CONVERSATION UNTUK ANAK-ANAK GRIYA YATIM DHUAFA PERMATA PAMULANG - Purnaningsih, Pari; Sukmawati, Nur Najibah; Isnaeni, Resti (Journal of Community Research and Service, 2022)
This Community Service (PkM) aims to apply the Role Play learning method in Basic English Conversation. This learning model can foster students' enthusiasm for learning and create fun English learning. This learning method is believed to be able to increase interest in learning English, especially for children because this method involves motion games that create fun which is closely related to children. The Role Play method is a learning model that requires students to play one's character. This model is a technique that allows students to explore realistic conditions, situations or events by interacting with other students in a managed manner to enhance the experience. This Community Service activity began with a pre-survey/observation in April 2022 and the core of this activity is conducting teaching and learning activities for the children of Griya Yatim Dhuafa Permata Pamulang by implementing Role Play which was held in mid-May 2022. The PkM results show there is an increase in students' motivation and enthusiasm in learning English so that it is expected to be a reference for educators in creating new nuances in learning English so as to create fun classes and achieve maximum learning goals.